(untitled) (Damascus University Journal of Historical Studies, 2022)
If it is linguistically or theoretically, the concept of license was not new in the educational departments as well as in the higher education department, but it is important to emphasize that the license was already known in our history. The student, the scholar and the license itself were including in the pillars of the license. However, its kinds were including a license in a specific book, topic, correspondence license, license in teaching and Iftaa, and general license. For its importance, the scientific licenses would be introduced in the tenth and eleventh Hijri centuries/ sixteenth and seventeenth centuries.